RELATIONSHIP BETWEEN ORGANIZATIONAL CLIMATE AND PERSONALITY ON COMMITMENT TO ORGANIZATIONS AIA AGENTS, AGENCY VISION ONE GROUP JAKARTA - Muryati Muryati; Ismuhadjar Ismuhadjar; Hari Muharam (UNIVERSITAS PAKUAN, 2022)
This study aims to find efforts to increase commitment to the organization through a study of the strength of the relationship between research variables, namely knowing, analyzing and revealing the relationship of organizational climate, personality relationship, and the two relationships together on commitment to the organization at AIA agents. Agency Vision One Group (VOG) in Jakarta. The method used in this research is a survey method with a correlational approach. This method is used to collect data from a number of agents within the company and at the same time, while the correlational approach is used to test statistically, research hypotheses, and describe analytically, systematically, factually and careful about the relationship between research variables. The variables studied in this study consisted of three, namely organizational climate, personality and commitment to the organization. Two independent variables are organizational climate and personality, while commitment to the organization is used as the dependent variable. The results showed that there is a positive relationship between Organizational Climate and Commitment to Organizations with a correlation coefficient ry.1 = 0.659 and a functional relationship equation = 6.260 + 0.971X1. Organizational Climate contributes 43.42% to Commitment to Organization. This means that the Organizational Climate contributes to the Commitment to the Organization. There is a positive relationship between Personality and Commitment to Organization with correlation coefficient ry.1 = 0.589 and functional relationship equation = 9.208 + 0.928X1. Personality contributes 34.69% to Commitment to the Organization. There is a positive relationship between Organizational Climate and Personality Together with Commitment to Organization with correlation coefficient R = 0.707 and functional relationship equation = 2.047 + 0.494X1 + 0.705X2. Organizational Climate and Personality together have a contribution of 24.10% to the Commitment to the Organization. This means that Organizational Climate and Personality together contribute to Commitment to the Organization. The more the Organizational Climate and Personality together it will increase the Commitment to the Organization